Effect of Levothyroxine on Pregnancy Outcomes in Pregnant Women With Hypothyroxinemia: An Interventional Study - Li, Guohua; Liu, Yang; Su, Xiujuan; Huang, Shijia; Liu, Xiaosong; Du, Qiaoling (Frontiers in Endocrinology, 2022)
Abstract Context: Adverse maternal outcomes and perinatal complications are associated with maternal hypothyroidism. However, the utility of levothyroxine (L-T4) in the treatment of pregnant women with hypothyroxinemia is unclear. Objective: This study aimed to evaluate the effects of L-T4 on maternal and perinatal outcomes in pregnant women with hypothyroxinemia. Methods: The nonrandomized interventional study was conducted at Shanghai First Maternity and Infant Hospital, Punan Hospital of Shanghai, and Beicai Community Health Center of Shanghai. The pregnant women with hypothyroxinemia from the first trimester were enrolled and divided into treatment and control groups. 463 taking L-T4 and 501 not administering L-T4 were analyzed in the study. All participants were screened for TPOAB/TGAB antibody status. Main outcome: The primary outcome of the study was the hypertensive disorder of pregnancy (HDP), measured as the proportion of HDP. In addition to this primary outcome, some secondary outcomes will be measured: miscarriage, gestational diabetes mellitus, premature rupture of membranes, placental abruption, intrahepatic cholestasis of pregnancy, fetal distress, macrosomia, and neonates admitted to the neonatal intensive care unit (NICU). The effects of L-T4 on the incidence of adverse pregnancy outcomes and perinatal complications were compared. Results: Multivariate logistic regression analysis showed that L-T4 treatment (adjusted odds ratio = 1.78 [95% CI = 1.00-3.16], p = 0.04) significantly reduced the incidence of miscarriage. Otherwise, lower neonates admitted to the NICU were strongly associated with the L-T4 group (adjusted odds ratio = 1.36 [95% CI = 1.01 – 1.83], p = 0.04). There were no significant differences in the incidence rates of other adverse maternal outcomes and perinatal complications between pregnant women with hypothyroxinemia receiving and those not receiving L-T4 treatment. Conclusion: The incidence of HDP was not significantly reduced using L-T4 in pregnant women with hypothyroxinemia. The results of this study also showed that L-T4 treatment significantly reduced the miscarriages rate and the proportion of newborns admitted to the NICU.